A decision support system for the choice of medium-capacity transit system - Tsai, Yu Luen (2010)
The rapid growth in many urban areas has resulted in traffic congestion, social inequity, and environmental problems. To control these problems, many cities have turned to urban transit systems to serve travel demand. The mass rapid rail transit (MRT) system has been implemented in many metropolitan areas. However, many cities do not have either the financial resources to afford a MRT system or the passenger demand to justify it. To improve public transport services, what is needed for such cities is an appropriate transit system which has higher capacity than a regular bus (RB) system and cheaper than the MRT. There are several medium-capacity transit systems that can meet this requirement. Such systems include Bus Rapid Transit (BRT), Light Rapid Transit (LRT), Guided Bus, Automated Guideway Transit (AGT) and Automated Light Rapid Transit (ALRT). Clearly, in the selection of an appropriate medium-capacity transit system for a study area, the option of retaining the existing transit system (usually RB) should also be considered as an alternative.